Language of the Goddess in Balkan Women's Circle Dance. (September 2019) - Shannon, Laura
The author narrates her journey to women's circle dances of the Balkans, and explores how they incorporate prehistoric signs which Marija Gimbutas called 'the language of the Goddess'. These symbolic images appear in archaeological artefacts, textile motifs, song words, and dance patterns, and have been passed down for thousands of years in nonverbal ways. The interdisciplinary approach of archaeomythology suggests that the images may carry ideas and values from the Neolithic cultures in which these dances are said to have their roots. Women's ritual dances affirm the Old European values which honoured the Goddess, the mother principle, and the cycles of life, and offer an extraordinary oasis of women's empowerment, even within patriarchal culture, indicating that the dances most likely originate in pre-patriarchal egalitarian matriarchy. For women today, even outside the Balkans, these women's ritual dances offer insight and meaning through an embodied experience of the values of the Goddess.